Issues and Solutions for Incorporating Islamic Education and Science into Schools and Higher Education Institutions - Fariq, Wan Muhammad; Karim, Nazir; Bakar, Abu (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2024)
Today, the debate over the integration of Islamic religious education and science in Indonesia's public schools and universities continues. They frequently navigated their own paths, ignoring each other's presence. This research attempts to identify the constraints and solutions to the integration of Islamic religious education and science in these institutions. The study employed a non-interactive qualitative approach, utilizing content analysis to examine various emerging issues found in books, documents, journals, and other articles. The study's findings revealed several obstacles to the integration of Islamic religious education and science in schools and tertiary institutions, such as the lack of relevant integration formulations, the absence of integration regulations, the scarcity of human resources, the division between religious and general material hours, and the lack of comprehensive teaching materials. Therefore, we can offer the following solutions: (1) formulating curriculum integration relevant to the Indonesian context; (2) establishing regulations or revising the National Education System Law; (3) fostering collaboration between PTU and PTAI; (4) preparing human resources in the form of focused and creative teachers; (5) reconstructing relevant teaching materials; and (6) providing adequate facilities and infrastructure.